The Relationship Between Visual Concentration Level and Handgrip Strength on Overhand Throw Accuracy - Hanif Irsyada; Siti Baitul Mukarromah; Said Junaidi (Indonesian Journal for Physical Education and Sport, 2025)
Softball is a sport that requires good basic throwing techniques. Players have a primary focus on catching the ball that is hit to their area and killing baserunners. In baseball and softball, hand strength and coordination are main factors in finding out the quality of a throw. The purpose of this study was to analyze the relationship between concentration level and grip strength on overhand throw accuracy. This research approach uses a quantitative method with a descriptive correlational approach. The sampling technique in this research used total sampling, which used all samples on the field. The sample used was female softball athletes from Semarang City with a total of 18 female athletes. The technique  of data analysis in this study was regression correlation, data normality test, linearity test, homogeneity test and hypothesis test using SPSS software version 25. Research conclusion: 1) There is no relationship between visual concentration and overhand throw accuracy. 2) There is a relationship between hand grip strength and overhand throw accuracy. 3) There is no relationship between visual concentration and hand grip strength to overhand throw accuracy.